Pawning Clove Plantation Land in Tolitoli Regency: The Perspective of Fiqh Muamalah - Fathul Khair; Muhammad Syakir Al Kautsar; Nurul Mahmudah (Nuban Jagadhita Centre, 2023)
Purpose: Implementation of pawning of clove plantation land in the Tolitoli community, the clove plantation land is temporarily owned by the pawn recipient, and the produce from the land is taken by the pawn recipient. The practice of clove pawning by the Tolitoli people greatly benefits those who receive the pledge of garden land and conversely causes losses to the pawnbroker or land owner. Methodology: This research is qualitative research. Findings: The practice of pawning clove land carried out by the community in Tolitoli Regency is not in accordance with mu’amalah fiqh. The discrepancy lies in the utilization of pawn goods and the results from clove land are fully utilized by the pawn recipient.